Analisis Butir Soal Ditinjau Dari Unsur Dimensi Pengetahuan Dan Jenjang Kognitif Soal Ujian Sekolah Tahun Pelajaran 2019/2020 dan 2020/2021 Mata Pelajaran IPA SDN 04 Kecamatan Pendopo - Suwai Batul Aslamiah Aslamiah; Irwan Koto; Endang Widi Winarni (UNIB Press, 2022)
This study aims to describe the percentage of knowledge dimensions and cognitive levels on school exam questions for the 2019/2020 and 2020/2021 Science subjects at SDN 04 Pendopo District. This type of research is descriptive quantitative research. The research subject is in the form of school exam questions for science subjects. The object of research is the percentage of knowledge dimensions and cognitive level of the questions. The research instrument was in the form of a sheet of knowledge dimension analysis and cognitive levels. The results show that: The highest percentage of knowledge dimensions on US IPA 2019/2020 questions are factual dimensions of 33 questions (82.50%), conceptual dimensions of 7 questions (17.50%), and procedural and metacognitive dimensions of 0% . The highest percentage of dimensions in the US IPA 2020/2021 questions is the factual dimension of 32 questions (80.00%), the conceptual dimension is 8 questions (20.00%) and the procedural and metacognitive dimensions are 0%. Percentage of cognitive level of US IPA 2019/2020 items for the highest cognitive level, namely applying (C3) as many as 16 questions (40%), understanding (C2) as many as 13 questions (32.50%), analyzing (C4) as many as 11 questions ( 27.50%), and remembering (C1), evaluating (C5), and creating (C6) did not appear. Percentage of cognitive level of US IPA items in 2020/2021 for the highest cognitive level, namely analyzing (C4) as many as 19 questions (47.50%), applying (C3) as many as 12 questions (30.00%), understanding (C2) as many as 8 questions (20.00%), evaluates (C5) as much as 1 question (2.50%). Thus, it can be concluded that the quality of the school exam questions for the 2019/2020 and 2020/2021 school year subjects in SDN 04 Pendopo District is viewed from the dimensions of knowledge and cognitive level of the questions.